PENGARUH JAMINAN DAN JANGKA WAKTU PINJAMAN TERHADAP KEPUTUSAN PENGAMBILAN KREDIT DI KSP SARI SEDANA NADI KECAMATAN BLAHBATUH KABUPATEN GIANYAR - Ni Made Yumita Sari; Ni Putu Yuliana Ria Sawitri; Made Ayu Desy Geriadi (Jurnal Bakti Saraswati (JBS), 2025)
Several researchers have found several factors that influence customer decisions, including collateral and loan terms. Similarly, in KSP Sari Sedana Nadi, collateral and loan terms are also one of the factors that influence credit decisions. The purpose of this study is to determine the simultaneous and partial effects of collateral and loan terms on credit decisions of KSP Sari Sedana Nadi. The sampling was conducted by chance sampling, i.e., 85 credit customers. The data were analyzed using multiple linear regression using computer tools in the form of SPSS 25.0 for Windows program. The results of the study showed that collateral and loan terms have a positive and significant impact on credit decisions of KSP Sari Sedana Nadi, simultaneously and partially. The significance of this study is that collateral and terms as a reference for partner institutions in formulating customer credit decision strategies and policies. it can be adjusted according to its target market and market needs.